Influence of electron emission effectiveness on characteristics of negative corona discharge - Bolotov, O.; Golota, V.; Ostroushko, V. (Вопросы атомной науки и техники, 2012)
To explain the results of experiments with negative corona in Trichel pulse mode it is proposed the assumption about decisive role of photoemission in supply of electrons from cathode. The results of numerical simulations correspond to experimental data and to simplified clear models.